Ultraviolet absorption of point defects in high purity bulk AlN - Shafiqul I. Mollik; M. E. Zvanut (AIP Advances)
Four point defects are analyzed in high purity bulk AlN crystals using electron paramagnetic resonance (EPR) spectroscopy. No EPR could be detected in the dark at temperatures as low at 4 K. The neutral donor and a newly detected center, M1, are observed during and after illumination with visible and near ultraviolet (UV) light, while two other defects are detected only during exposure to near and deep UV radiation. One is the neutral charge state of the carbon acceptor, and it, along with a second newly observed center, M2, are observed between 4 and 4.7 eV. Both M1 and M2 represent high spin centers and are stable in their EPR active charge state up to 373–473 K (100–200 °C). These centers must be considered as AlN advances toward a functional photonic and electronic material.